Adults and Family as Supportive of Adolescent Sexual Development in the Age of Smartphones? Exploring Cybersexual Violence Victimization, Pornography Use, and Risky Sexual Behaviors. - Rivas-Koehl, Matthew; Valido, Alberto; Espelage, Dorothy L.; Lawrence, Timothy I. (Archives of Sexual Behavior, 2023)
Among adolescents, engagement in risky sexual behavior is an important public health concern. Research has begun to explore the impact of adolescents' online experiences with their social and behavioral health as approximately 95% of adolescents have access to a smartphone connected to the internet. However, little research has specifically examined how online experiences impact sexual risk behaviors among adolescence. To fill gaps in the existing research, the current study sought to investigate the association between two potential risk factors and three sexual risk behavior outcomes. We examined how experiencing cybersexual violence victimization (CVV) and using pornography during early adolescence was associated with condom use, birth control use, and use of alcohol and drugs before sex among U.S. high school students (n = 974). Additionally, we explored multiple forms of adult support as potential protective factors of sexual risk behaviors. Our findings suggest that CVV and porn use may be associated with risky sexual behaviors for some adolescents. In addition, parental monitoring and support from adults at school may be two ways to support healthy adolescent sexual development.